Public Employment, Collective Bargaining and the Conventional Wisdom : Canada and U.S.A. - Cunningham, W. (Relations industrielles / Industrial Relations, 1966)
The author states that the conventional wisdom has viewed collective bargaining in the public service as unnecessary, impractical and illegal. And he adds that, in general, and until recently, the prevailing practices in the United States and Canada have been in close harmony with the conventional wisdom. But the restless change of events threatens the existing state of affairs, described by the conventional wisdom, with progressive obsolescence. And the author answers the two following questions: Can the industrial relations system of the private sector be applied to public employment? To what extent does the nature of government employment raise unique problems?The enemy of the conventional wisdom is not ideas but the march of events.J.K. GALBRAITH,« The Affluent Society »